Reduction Pilot Contamination in Downlink Multi-Cell for Massive MIMO Systems - Salh, Adeeb; Audah, Lukman; Mohd Shah, Nor Shahida; Hamzah, Shipun Anuar (International Journal of Integrated Engineering, 2019)
Massive multiple- input–multiple- output has become an important fifth-generation (5G) wireless communication system because it improves transmitted spectral efficiency. In this paper, we obtained the maximal spectral efficiency by improving transmission performance in cell edges. This was achieved by using pilot reuse sequences from all available pilots in order to mitigate the pilot contamination and to suppress interference between adjacent cells. In addition, we investigated the impacts of pilot contamination on the received signal-to-interference-noise ratios (SINR) of users and employed different pilot reuse. We propose a new method called cell-edge-aware maximum ratio transmission (MRT), zero forcing (ZF), and return zero forcing (R-ZF). These were the precoders that employed less spatial dimensions and were able to suppress adjacent cells interference of the maximally vulnerable active user. We conclude that the large pilot reuse value between neighboring cells increased the gain, avoided interference between adjacent cells, and gave the maximal spectral efficiency. Consequently, the R-ZF was better than ZF and MRT because it was able to suppress the SINR.